2006
DOI: 10.1080/03014460600578631
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in affluent school children of Punjab

Abstract: In the present cross-sectional study, an attempt has been made to report the prevalence of overweight and obesity in school-going children of the affluent families of Punjab. A total of 1000 children (490 boys and 510 girls) were measured for height and weight. Overweight and obesity were assessed using age and sex-specific body mass index (BMI) cut-off points. In the present study, 12.24% boys and 14.31% girls were overweight, and 5.92% boys and 6.27% girls were obese. The prevalence of overweight and obesity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
52
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 11 publications
5
52
0
1
Order By: Relevance
“…M et al reported that risk of increasing childhood obesity has direct relationship with parental obesity. [12][13][14][15] All these findings were similar to the several studies conducted in India as well as worldwide. Very glaringly most of these studies were conducted in urban areas.…”
Section: Discussionsupporting
confidence: 80%
“…M et al reported that risk of increasing childhood obesity has direct relationship with parental obesity. [12][13][14][15] All these findings were similar to the several studies conducted in India as well as worldwide. Very glaringly most of these studies were conducted in urban areas.…”
Section: Discussionsupporting
confidence: 80%
“…The result similar to as reported by Khadilkar et al 16 Prevalence of obesity among male 17(20.2%) was slightly higher vs. female 16(15.4%) but statistically not significant and similar to the result reported by Khadilkar et al 12.4 vs 9.9%, Harish Ranjani et al, and Sidhu et al 5 vs 6 %. 9,16,17 There was statistically significant difference (p <0.001) between urban and rural groups for the distribution of BMI categories A and B.…”
Section: Discussionmentioning
confidence: 99%
“…After adjusting for individual sociodemographic characteristics, Punjab was found to have the highest average BMI and the highest prevalence of overweight. This may be due, at least in part, to agricultural advances that have made the area a net food exporter (Tiwana et al, 2005), as well as cultural shifts in which sedentary behavior and a calorie-dense diet have gained wide appeal (Sidhu et al, 2006). Many states in India's northeast, namely Arunachal Pradesh, Manipur, Mizoram, and Assam, had prevalences of both overweight and underweight which were below the national mean.…”
Section: Discussionmentioning
confidence: 99%